1964
DOI: 10.1093/aesa/57.1.127
|View full text |Cite
|
Sign up to set email alerts
|

Host-Plant Selection by the Mexican Bean Beetle, Epilachna varivestis1

Abstract: The Mexican bean beetle, Epilachna varivestis Mulsant, feeds selectively on certain species of Phaseolus to the exclusion of the remaining representatives of this and other genera of beans. In a study of the chemical factors underlying this selective feeding, the phagostimulant fraction in the seeds of P. vulgaris was isolated and identified as sucrose. Bioassay of 13 sugars and 15 amino acids showed that only sucrose and, to a lesser degree, its hexose components induced feeding by the beetle. The seeds as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 12 publications
(15 reference statements)
1
23
0
Order By: Relevance
“…Mineral balance, which encompasses both ratios and levels, is important to plant biochemical function. Either deficient or excessive levels of certain plant nutrients can slow the production of more complex plant chemicals, potentially leading to the accumulation of simpler metabolic building blocks, such as free amino acids and sugars, which can provide an enriched diet for insect herbivores (Waldbauer, 1968) and/or stimulate oviposition or feeding (Augustine et al, 1964 ). In this manner, mineral imbalance may increase crop susceptibility to pests.…”
Section: Resultsmentioning
confidence: 99%
“…Mineral balance, which encompasses both ratios and levels, is important to plant biochemical function. Either deficient or excessive levels of certain plant nutrients can slow the production of more complex plant chemicals, potentially leading to the accumulation of simpler metabolic building blocks, such as free amino acids and sugars, which can provide an enriched diet for insect herbivores (Waldbauer, 1968) and/or stimulate oviposition or feeding (Augustine et al, 1964 ). In this manner, mineral imbalance may increase crop susceptibility to pests.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that it is possible to divert insect pests from soybean crop by growing an attractive trap in a smaller area for example leaf bean beetles, Cerotoma trifurcate, (Pedigo, 1989), Mexican bean beetles, Eplachna varivestis, (Augustine et al, 1964;Rust, 1977;Mcpherson, 1983), stink bugs, Nezara viridula, (McPherson and Newsom, 1984;Kobayshi and Cosenza, 1987), and scarabaeid beetles, Anomela cupripes and A. expansa, (Talekar and Nurdin, 1991). However, none of these studies have used a transgenic crop to divert insect pests.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as attractants and repellents (e.g., Hedin et al, 1974;Augustine, 1962;Augustine et al, 1964) can be independently evaluated rising the AFD (see Fig. The no-choice bioassay does not measure long-or medium-range orientation and recognition, because movement is confined by the arena.…”
Section: Discussionmentioning
confidence: 99%
“…This insect is easy to rear and has been extensively studied (List, 1921;Thomas, 1924;Howard, 1941;Augustine, 1962; Lapi-* Present address: 1210 N.E., 20th Place, Gainesville, Fla. 32601, U.S.A. dus et al, 1963;Nayar & Fraenkel, 1963;Augustine et al, 1964;Kogan, 1972Kogan, , 1973Smith et al, 1979). Our "testcase" insect was the Mexican bean beetle, Epilachna varivestis Mulsant (Coleoptera; Coccinellidae).…”
mentioning
confidence: 99%